2023
DOI: 10.1097/pec.0000000000002906
|View full text |Cite
|
Sign up to set email alerts
|

Accidental and Abusive Mandible Fractures in Infants and Toddlers

Abstract: Objective: Mandible fractures are uncommon injuries in infants and young children and may raise concern for nonaccidental trauma. Our study describes several children with mandible fractures to identify features that might differentiate abuse from accident.Methods: Records and imaging were reviewed for children aged 24 months and younger who were diagnosed with mandible fractures at 2 tertiary pediatric care centers. Twenty-one cases were included, 8 of whom had formal child abuse consultations. Cases were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported MCF to be common in children, although it is relatively uncommon to see these injuries in infants [10][11][12]. Perhaps, owing to the elasticity of bone as well as limited mobility prior to 6 months of age, MCF have been very rarely reported in the infant age group [8,13]. Recent limited cases of MCF in infants have been included as part of case series of all pediatric patients with MCF [4,8,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported MCF to be common in children, although it is relatively uncommon to see these injuries in infants [10][11][12]. Perhaps, owing to the elasticity of bone as well as limited mobility prior to 6 months of age, MCF have been very rarely reported in the infant age group [8,13]. Recent limited cases of MCF in infants have been included as part of case series of all pediatric patients with MCF [4,8,14].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, owing to the elasticity of bone as well as limited mobility prior to 6 months of age, MCF have been very rarely reported in the infant age group [8,13]. Recent limited cases of MCF in infants have been included as part of case series of all pediatric patients with MCF [4,8,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations